IMPACT OF ECONOMIC AND NON-ECONOMIC FACTORS ON THE SUSTAINABILITY OF THE PENSION SYSTEM IN CROATIA - Maja Vretenar Cobović; Branko Matić (Ekonomski Vjesnik, 2017)
The pension system is very important in the context of the social security of every individual or the society in which it is located. Maintaining the stability of this system is one of the fundamental problems, both for Croatia and for other EU member states. The aim of this paper is to analyse the efficiency and sustainability of the existing pension system in the Republic of Croatia and the identification of key parameters which determine its further development. The authors’ comparative analysis of the Croatian pension system with the pension systems of individual EU Member States investigates the compliance of the Croatian pension insurance with the European social model, and the impact of economic factors on the sustainability of this system. Through the survey, authors explored the impact of non-economic factors on the pension system, and received relevant information about the attitudes of stakeholders (users) of the current pension system, their awareness and confidence in the system, the willingness to participate in certain forms of pension insurance (in particular those that are voluntary) and expectations of the insured on the return on investment, and the threshold of satisfaction on investments in pension funds.